Development and preliminary evaluation of a novel physician-report tool for assessing barriers to providing care to autistic patients - Chloe Walsh; Sinéad Lydon; Rosemary Geoghegan; Cornelia Carey; Michael Creed; Lauren O'Loughlin; Ellen Walsh; Dara Byrne; Paul O'Connor (BMC, 2021)
Abstract Background Individuals on the autism spectrum face significant disparities in health and physicians often report difficulties in providing care to autistic patients. In order to improve the quality of care autistic individuals receive, it is important to identify the barriers that physicians experience in providing care so that these may be addressed. This paper reports the initial development and preliminary evaluation of a physician-report 'Barriers to Providing Healthcare' measurement tool. Method An established taxonomy of healthcare barriers for autistic individuals informed the initial draft of a 22-item measurement tool. This measurement tool was distributed to physicians working in various healthcare specialties and settings. Exploratory factor analysis (EFA) was conducted to determine the construct validity of the tool; discriminant validity between, and internal consistency of, the resultant factors were assessed. Multiple regressions were used to explore variables potentially associated with barriers endorsed by physicians. Results A total of 203 physicians were included in the analyses. The EFA resulted in a 17-item tool with three distinct factors which explained 37.6% of the variance: 1) Patient-related barriers (Cronbach's α = 0.83; e.g., the patient's reactivity to the healthcare environment); 2) Healthcare provider (HCP)/family-related barriers (Cronbach's α = 0.81; e.g., a lack of providers willing to work with autistic patients); and 3) System-related barriers (Cronbach's α = 0.84; e.g., there is a lack of support for patients and families). Discriminant validity between the factors was adequate (r < .8). The barriers that were most frequently endorsed as occurring 'often' or 'very often' included a lack of support for patients and families (endorsed by 79.9% of physicians); communication difficulties (73.4%); and a lack of coordination between services (69.9%). The regression analyses identified no significant associated variables. Conclusion A preliminary version of a novel physician-report tool to assess barriers to providing care to autistic patients has been developed although further validation work is required. The use of this tool will help physicians to identify issues specific to different medical specialities and healthcare settings. This information may help identify the supports physicians require to recognise and implement the required accommodations. Future research which elucidates barriers to healthcare provision for autistic patients is required to support systemic change in healthcare so as to improve care experiences and health outcomes for people on the autism spectrum.